PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA RESTORAN DAPHUBU KAMPUNG ACEH DI PAMULANG BARAT - Firman Nur Kholik; Dana (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of product quality and service quality on customer satisfaction at the Daphubu Kampung Aceh restaurant in West Pamulang, both partially and simultaneously. The research method used is quantitative. The population in the study was 7,473 respondents. With a sampling technique using random sampling, a sample of 99 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The research results show that product quality has a significant effect on customer satisfaction with a simple regression equation Y = 12.512 + 0.226X1. Hypothesis testing obtained t value > t table or (4.251 > 1.985). Thus, Ho1 is rejected and Ha1 is accepted, meaning that there is a significant influence of product quality on customer satisfaction. Service Quality has a significant effect on Customer Satisfaction with the simple regression equation Y = 12.512 + 0.505X2. Hypothesis testing obtained a calculated t value > t table or (7.653 > 1.985). Thus, Ho2 is rejected and Ha2 is accepted, meaning that there is a significant influence of Service Quality on Customer Satisfaction. Product Quality and Service Quality on Customer Satisfaction with the multiple regression equation, namely Y = 12.512 + 0.226X1 + 0.505X2. Hypothesis testing obtained calculated F value > F table or (57.983 > 3.091). Thus, Ho3 is rejected and Ha3 is accepted, meaning that there is a significant simultaneous influence of Product Quality and Service Quality on Customer Satisfaction.